2021
DOI: 10.1002/lpor.202100175
|View full text |Cite
|
Sign up to set email alerts
|

Photonic Frequency Conversion of OFDM Microwave Signals in a Wavelength‐Scale Optomechanical Cavity

Abstract: Optomechanical (OM) cavities enable coupling of near‐infrared light and GHz‐frequency acoustic waves in wavelength‐scale volumes. When driven in the phonon lasing regime, an OM cavity can perform simultaneously as a nonlinear mixer and a local oscillator—at integer multiples of the mechanical resonance frequency—in the optical domain. In this work, this property is used to demonstrate all‐optical frequency down‐ and up‐conversion of MHz‐bandwidth orthogonal frequency division multiplexed signals compliant with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Furthermore, the platform developed here is based on nanocrystalline silicon, which is more affordable than crystalline silicon and more versatile, with the possibility to, for example, fabricate multilayer systems. Besides application in quantum networks to transfer qubits via optical links, the possibility to have interacting microwave and optical signals in CMOS silicon chips operating at room temperature opens new avenues in integrated microwave photonics, with prospects for application in all-optical processing in wireless networks . Finally, these results are very encouraging to advance the use of multistate variables in a single chip for optimal information transmission and processing.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, the platform developed here is based on nanocrystalline silicon, which is more affordable than crystalline silicon and more versatile, with the possibility to, for example, fabricate multilayer systems. Besides application in quantum networks to transfer qubits via optical links, the possibility to have interacting microwave and optical signals in CMOS silicon chips operating at room temperature opens new avenues in integrated microwave photonics, with prospects for application in all-optical processing in wireless networks . Finally, these results are very encouraging to advance the use of multistate variables in a single chip for optimal information transmission and processing.…”
Section: Discussionmentioning
confidence: 94%
“…We have identified that the synchronization mechanism is of the phase-locking type, instead of suppression of the natural dynamics. Synchronization of the SP at subharmonics of the external signal has revealed as a very effective mechanism, in some cases even more than at the main harmonic, thus suggesting the possible use of this system for frequency division purposes 28,29 , which often demand low-power consumption and wide-band operation 30 .…”
Section: Discussionmentioning
confidence: 99%
“…All the mechanical modes show reasonably large values of g 0 /2π up to 600 kHz which enable efficient transduction into a driving optical signal. Multiple applications can be envisaged, including multimode phonon lasers 8 , frequency up-and down-conversion of multiple wireless signals 26 or building chiral nano-optomechanical networks 7 .…”
Section: Discussionmentioning
confidence: 99%
“…This could be particularly helpful in quantum applications at cryogenic temperatures, because of the enhancement of the mechanical Q factor in these conditions 25 . A reliable route to multiple phonon modes with large coupling rates would also open the door to versatile all-optical OM-based microwave signal synthesis 24 and processing 26 , which is especially valuable for application in wireless systems, in particular those requiring extreme compactness and lightweight (satellite communications) 27 .…”
Section: Introductionmentioning
confidence: 99%